Modeling an Inflammation‐Related Depressive Phenotype in Mice Using Bacille Calmette‐Guérin. Issue 1 (28th March 2018) - Platt, Brian J.; Clark, Janet A.
Abstract: The relationship between inflammation and neuropsychiatric symptoms is of interest to the scientific community for several reasons. A substantial subset of patients suffering from major depressive disorder also exhibit evidence of chronic inflammation including elevated levels of circulating pro‐inflammatory cytokines. Immune‐mediated inflammatory diseases and immunotherapy can result in depressive symptoms in some patients. Recent evidence suggests that the chronic inflammation may play a role in the pathophysiology of the depressive state, although the specific biological mechanisms are not clear. Herein we describe a model of an inflammation‐related depressive phenotype in mice using the tuberculosis vaccine, bacille Calmette‐Guérin, to induce chronic inflammation and a subsequent depressive phenotype which is assessed using the tail‐suspension test. The model provides an avenue to study not only the molecular and biochemical changes that may be associated with the development of the depressive phenotype, but also pharmacological manipulations of the phenotype. Curr. Protoc. Neurosci . 65:9.46.1‐9.46.10. © 2013 by John Wiley & Sons, Inc.